The Mayor of Hell Based on a Story by Islin Auster - Mayo, Archie; McGill, Barney; Cagney, James; Evans, Madge; Byron, Arthur (Warner, 2008)
You scratch my back, I'll scratch yours. Politicos award gangster Patsy Gargan a cushy job as a honcho at a woefully run boys reform school. No experience necessary. No expectations. No problems. But firebrand Patsy (James Cagney) runs up against plenty of problems in this impassioned Depression-era mix of social conscience filmmaking and the gangster genre. He sees something in the kids - himself. He, too, was raised in the slums. And he decides to defy everyone to give the kids opportunities he never had. Yet all the good Patsy does could collapse when he missteps into his life of crime. This punchy tale was retold in films featuring the Dead End Kids: "Crime School" (with Humphrey Bogart) and "Hell's Kitchen". [Cover]
Keywords: DVD-Video